Pengembangan Multimedia Interaktif Menggunakan Articulate Storyline pada Mata Pelajaran IPAS Kelas V SD - Yudhani, Abelta Putri; Hendri, Nofri; Pratiwi, Rahmi; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop interactive multimedia using Articulate Storyline in the subject of social sciences for grade V of elementary school, especially as a solution to the lack of learning media used in the teaching and learning process. This study uses a Research & Development (R&D) approach with the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. The data collected includes qualitative and quantitative data. The results of the study showed that the average validation score by material experts was 4.91 with the category of